RESPON PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L) Merril GALUR GH-63 YANG DIBERI PUPUK HAYATI PADA GAMBUT PEDALAMAN: GROWTH AND YIELD RESPONSE OF SOYBEAN (Glycine max (L) Merril GH-63 STRAINS GIVEN BIOLOGICAL FERTILIZER ON INLAND PEAT - Rumbang, Nyahu; Oemar, Oesin; Vetrani Asie, Kambang; Darung, Untung; Riak Asie, Erika; Surawijaya, Panji; Safitri, Wanda (Fakultas Pertanian Universitas Palangka Raya, 2025)
The purpose of this study was to study the effect of organic fertilizer on the growth and yield of GH-63 soybeans on inland peat. The peat used was taken from Kalampangan Village and the land conditions had never been used for agricultural cultivation. The study was conducted in the Peat Techno Park area of ​​Palangka Raya University. Using a Completely Randomized Design, with 4 treatments of Rhizoka compound organic fertilizer dosage, namely H0 = 0 g.kg seed-1, H1 = 10 g.kg seed-1, H2 = 20 g.kg seed-1, H3 = 30 g.kg seed-1. Each treatment was repeated 5 times and because there were destructive and non destructive observations, the study was conducted in 2 (two) equal series. Data were analyzed by analysis of variance at the 5% and 1% levels. If the results of the analysis of variance indicate a significant effect, it is continued with the BNJ test at the 5% level. The results showed that treatment H3 = 30 g.kg seed-1 as the best treatment in all parameters, namely leaf area (77.03 cm2), effective root nodule weight (1.015 g), root dry weight (1.04 g), loss dry weight (3.71 g), root extinction ratio (3.64 g), number of seeds (1.98 seeds) and seed weight (1.15 g) compared H0 = 0 g.kg seed-1. The dose dose of biofertilizer is 30 g.kg seed-1 as the best dose for the growth and yield of GH-63 soybean plants on inland peat.